1991
DOI: 10.1111/j.1365-2621.1991.tb14597.x
|View full text |Cite
|
Sign up to set email alerts
|

Precooking Method Affects Warmed‐over Flavor of Broiler Breast Patties

Abstract: Broiler breast patties cooked in a water bath (85°C vs 95°C) or oven (160°C vs 180°C) to an internal temperature of 83°C were stored at 3°C for 3 days, reheated, and evaluated by headspace GC and thiobarbituric acid (TBA) methods. Cooking temperature within the same cooking medium had no effect on TBA values or headspace GC profiles of cooked, stored samples. During post-cooking storage TBA values and several headspace volatiles increased. The changes were more severe in oven-cooked than water-cooked patties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…McCarthy et al (2001) reported cooking of pork patties significantly increased thiobarbituric acid reactive substances (TBARS) values with a 4-fold increase in oxidation levels being recorded in raw patties upon cooking. The rapid development of off flavour in cooked meat is commonly described as 'warmed-over flavour' and is generally considered to be due to the oxidation of phospholipids located in the cell membranes (Su et al 1991). Patil et al (2003) observed the increase in TBA values when the chevon was aged at 1°C for 12 and 15 days.…”
Section: Introductionmentioning
confidence: 97%
“…McCarthy et al (2001) reported cooking of pork patties significantly increased thiobarbituric acid reactive substances (TBARS) values with a 4-fold increase in oxidation levels being recorded in raw patties upon cooking. The rapid development of off flavour in cooked meat is commonly described as 'warmed-over flavour' and is generally considered to be due to the oxidation of phospholipids located in the cell membranes (Su et al 1991). Patil et al (2003) observed the increase in TBA values when the chevon was aged at 1°C for 12 and 15 days.…”
Section: Introductionmentioning
confidence: 97%
“…Techniques being used by the U.S. Department of Agriculture Food Safety and Inspection Service (FSIS) include the protein coagulation test for beef and pork products heat-processed to temperatures below 65 °C (USDA-FSIS, 1986a), a residual acid phosphatase activity method to determine the required internal temperature (68.8 °C) of imported hams, picnics, and luncheon meat (USDA-FSIS, 1986b), and the bovine catalase test developed by Eye (1982) for the detection of under processing (below 62.8 °C) of rare beef and canned beef. The enzymatic activity or the protein solubility becomes too low at 71.1 °C, the required temperature for poultry During cooking of muscle food, many flavor compounds are generated (Wasserman, 1979;Ramaswamy and Richards, 1982;Ang, 1991; Ang and Lyon, 1990). Gas chromatographic methods (GC) have been used in studies concerning poultry flavors (Ramaswamy and Richards, 1982;Dupuy et al, 1987) and volatile compounds as affected by heating treatments (Wu and Sheldon, 1988;Smith et al, 1987;Su et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity or the protein solubility becomes too low at 71.1 °C, the required temperature for poultry During cooking of muscle food, many flavor compounds are generated (Wasserman, 1979;Ramaswamy and Richards, 1982;Ang, 1991; Ang and Lyon, 1990). Gas chromatographic methods (GC) have been used in studies concerning poultry flavors (Ramaswamy and Richards, 1982;Dupuy et al, 1987) and volatile compounds as affected by heating treatments (Wu and Sheldon, 1988;Smith et al, 1987;Su et al, 1991). A rapid, static headspace GC method using a packed column was developed for studying oxidative changes of cooked chicken meat (Ang and Young, 1989) and the influence of EPT and packaging methods on volatiles from cooked broiler leg patties (Ang and Huang, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…To avoid overheating samples, Ang and Young (1989) reported a static headspace GC method using a packed column with chicken samples conditioned at 8OC for 30 min before the injection. This method has been applied to studies concerning the oxidative stability of heated chicken meat (Ang and Lyon 1990;Su et al 1991). The sample conditioning temperature was later modified to be 60C for studies on temperature effect of chicken meat heated to EFTS between 60 and 85C (Ang and Huang 1993).…”
Section: Methods For Evaluation Of Muscle Oxidationmentioning
confidence: 99%